Conformational transitions of alternating purine-pyrimidine DNAs in perchlorate ethanol solutions - Vorlícková, M (Biophysical journal, 1995)
Conformational transitions of poly(dA-dC).poly(dG-dT), poly(dA-dT).poly(dA-dT), and other alternating purine-pyrimidine DNAs were studied in aqueous ethanol solutions containing molar concentrations of sodium perchlorate, which is a novel solvent stabilizing non-B duplexes of DNA. Using CD and UV absorption spectroscopies, we show that this solvent unstacks bases and unwinds the B-forms of the DNAs to transform them into the A-form or Z-form. In the absence of divalent cations poly(dA-dC).poly(dG-dT) can adopt both of these conformations. Its transition into the Z-form is induced at higher salt and lower ethanol concentrations, and at higher temperatures than the transition into the A-form. Submillimolar concentrations of NiCl2 induce a highly cooperative and slow A-Z transition or Z-Z' transition, which is fast and displays low cooperativity. Poly(dA-dT).poly(dA-dT) easily isomerizes into the A-form in perchlorate-ethanol solutions, whereas high perchlorate concentrations denature the polynucleotide, which then cannot adopt the Z-form. At low temperatures, however, NiCl2 also cooperatively induces the Z'-form in poly(dA-dT).poly(dA-dT). Poly(dI-dC).poly(dI-dC) is known to adopt an unusual B-form in low-salt aqueous solution, which is transformed into a standard B-form by the combination of perchlorate and ethanol. NiCl2 then transforms poly(dI-dC).poly(dI-dC) into the Z'-form, which is also adopted by poly(dI-br5dC).poly(dI-br5dC).
Keywords: roztoky; denaturace nukleových kyselin; sekvence nukleotidů; Poly dA-dT; Nucleic Acid Conformation; Perchlorates; polydeoxyribonukleotidy; biofyzika; sloučeniny sodíku; techniky in vitro; Circular Dichroism; Nucleic Acid Denaturation; Spectrophotometry, Ultraviolet; konformace nukleové kyseliny; poly dA-dT; Solutions; biofyzikální jevy; Biophysical Phenomena; Biophysics; Sodium Compounds; ethanol; cirkulární dichroismus; Ethanol; In Vitro Techniques; DNA; perchloráty; Base Sequence; Polydeoxyribonucleotides; spektrofotometrie ultrafialová